2019
DOI: 10.1038/s41598-019-43201-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Repurposed Drug Diosmin with Amoxicillin-Clavulanic acid Causes Synergistic Inhibition of Mycobacterial Growth

Abstract: Effective therapeutic regimens for the treatment of tuberculosis (TB) are limited. They are comprised of multiple drugs that inhibit the essential cellular pathways in Mycobacterium tuberculosis ( Mtb ). The present study investigates an approach which enables a combination of Amoxicillin-Clavulanic acid (AMC) and a repurposed drug for its synergistic effect towards TB treatment. We identified Diosmin (DIO), by targeting the active site residues of L,D-transpeptida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Further docking and molecular dynamic investigation not only confirmed the primary inverse virtual screening predictions but also revealed that some inactive derivatives can possibly modify the PBP2a allosteric site and hence, serve as adjuvants to reverse MRSA resistance toward β-lactams antibiotics (e.g., ampicillin 23). These findings were also in great accordance with the previous studies that highlighted polyhydroxylated flavonoids as promising synergistic agents to β-lactams antibiotics [16,21,23].…”
Section: Discussionsupporting
confidence: 92%
“…Further docking and molecular dynamic investigation not only confirmed the primary inverse virtual screening predictions but also revealed that some inactive derivatives can possibly modify the PBP2a allosteric site and hence, serve as adjuvants to reverse MRSA resistance toward β-lactams antibiotics (e.g., ampicillin 23). These findings were also in great accordance with the previous studies that highlighted polyhydroxylated flavonoids as promising synergistic agents to β-lactams antibiotics [16,21,23].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we also realized that hesperidin and diosmin performed better binding interaction to the HR2 binding domain of S2 (S2 sub unit: 6LXT) ( Figure 4B) compared to other tested compounds. Pushkaran, et. al., 2019 Anticancer Inhibits the proliferation of MCF 7 GFP Tubulin cells and LNCaP cells.…”
Section: Resultsmentioning
confidence: 99%
“…39 The docking protocol using the GLIDE module has been successfully implemented in our previous studies. [40][41][42][43] The bioactive phytochemicals from different medicinal plants were ranked based on their docking score (or binding affinity) against the SARS-CoV-2 protein targets. The best phytochemicals were further analyzed using the PyMol and Discovery Studio visualizer to understand its molecular mechanism of action for SARS-CoV-2 infections.…”
Section: Molecular Docking Of the Phytochemicals Towards Sars-cov-2 Tmentioning
confidence: 99%